Algorithm for Evaluating Errors in Recognition of Materials in X-Ray Testing System Containing X-Ray Sandwich Detectors; Russian Journal of Nondestructive Testing; Vol. 58, iss. 1 - Udod V. A. Viktor Anatolievich (2022, 2022)
Title screen